2022
DOI: 10.3389/fnagi.2021.783431
|View full text |Cite
|
Sign up to set email alerts
|

Selective and Inverse U-Shaped Curve Alteration of the Retinal Nerve in Amyotrophic Lateral Sclerosis: A Potential Mirror of the Disease

Abstract: Introduction: Alterations in the visual pathway involving the retina have been reported in amyotrophic lateral sclerosis (ALS) but they lack consistency and subgroup analysis. We aimed to assess the retinal nerve fiber layer (RNFL) and retinal ganglion cells (RGCs) alterations in different stages of ALS patients and their association with ALS progression parameters.Methods: The study population consisted of 70 clinically diagnosed ALS patients and 55 age, sex matched controls. All of them underwent ophthalmic … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 51 publications
1
6
0
Order By: Relevance
“…Moreover, phenotypic analysis of the microglia showed an M1 phenotype or proinflammatory state of microglia, as the cells were intensely labeled with anti-IFNγ and anti-IL-1β but did not stain with the characteristic M2 markers (anti-arginase 1 and anti-IL-10) [103]. The significant decrease in the total number of Brn3a + RGCs at 120 days of illness would be consistent with the damage observed in the RGCs of the ALS models discussed above [37,101,102], as well as with the thinning of the peripapillary retinal nerve fiber layer (pRNFL), observed by OCT, in ALS patients compared with controls [36][37][38][39][40][41][42][43][44]. Consequently, these data would support that, in ALS, not only are motor neurons affected but also RGC loss occurs, considering this disease as a multisystemic disease [103].…”
Section: Summary Of Retinal Changes In Amyotrophic Lateral Sclerosis ...supporting
confidence: 55%
See 1 more Smart Citation
“…Moreover, phenotypic analysis of the microglia showed an M1 phenotype or proinflammatory state of microglia, as the cells were intensely labeled with anti-IFNγ and anti-IL-1β but did not stain with the characteristic M2 markers (anti-arginase 1 and anti-IL-10) [103]. The significant decrease in the total number of Brn3a + RGCs at 120 days of illness would be consistent with the damage observed in the RGCs of the ALS models discussed above [37,101,102], as well as with the thinning of the peripapillary retinal nerve fiber layer (pRNFL), observed by OCT, in ALS patients compared with controls [36][37][38][39][40][41][42][43][44]. Consequently, these data would support that, in ALS, not only are motor neurons affected but also RGC loss occurs, considering this disease as a multisystemic disease [103].…”
Section: Summary Of Retinal Changes In Amyotrophic Lateral Sclerosis ...supporting
confidence: 55%
“…Even a significant interocular difference of the P100 in ALS patients was demonstrated in a study of visual evoked potentials [33], similar to the existing asymmetry in the CNS of these patients [14]. Some researchers have also analyzed changes in the visual pathway (a nonmotor neuron area) using optical coherence tomography (OCT) in ALS patients [35][36][37][38][39][40][41][42][43][44], finding different changes in the retina and optic nerve, some with contradictory results, stressing the importance of classifying patients by both stage and type of ALS, given the high heterogeneity of the disease.…”
Section: Introductionmentioning
confidence: 95%
“…These studies indicate that pathological changes of visual pathway were solid evidence in neurodegenerative diseases. Recently, reported alteration of the retinal nerve in ALS was reported implied that the ALS visual pathway may be damaged 49 . The effects of genetic factors on pathological changes in the visual pathway in ALS require more investigation.…”
Section: Discussionmentioning
confidence: 99%
“…Thinning of the RNFL is either due to death of the ganglion cells or Wallerian degeneration secondary to death of the cortical neurons. [ 13 , 18 20 ]…”
Section: Discussionmentioning
confidence: 99%
“…[ 12 ] found some evidence of asymmetric RNFL involvement. Although several studies[ 18 ] have shown asymmetric CNS involvement in ALS, our study is the first in India to assess ALS’s asymmetricity by evaluating the thickness of the RNFL in the right and left eyes. In other words, our study proves that this laterality is not confined to the motor system.…”
Section: Discussionmentioning
confidence: 99%